2006
DOI: 10.1002/art.21694
|View full text |Cite
|
Sign up to set email alerts
|

Profile of arthritis disability: II

Abstract: Objective. Arthritis is the most common chronic condition and the most common cause of disability among older US adults. We studied social participation, disabilities in many life domains, accommodations used (buffers), and accommodations needed (barriers) for US adults with arthritis disability compared with adults with disability from other conditions. Methods. The data source is the National Health Interview Survey Disability Supplement Phase Two. Arthritis-disabled individuals named arthritis as the main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…Numerous studies (16 -20) indicated pain and severity of functional disability as limiting duration and type of employment, although other studies indi-cated specific symptoms such as pain, joint function, and laboratory findings as nonpredictors of work limitations and cessation (5). Other factors associated with vocational success for persons with arthritis include support of coworkers, supervisors, and family members; perceived high job status; positive attitudes toward the job; workstation modifications; satisfactory transportation; and selfemployment (13,(15)(16). More common and effective accommodations reported were the ability to alter work hours, flexible scheduling, the ability to control the pace of work tasks, participation in decision making, fewer work place limitations (e.g., sitting and standing long periods, lifting, reaching, and repetitive tasks), the ability to modify tasks and workstations, assistance from others, medications, and changing jobs (21,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies (16 -20) indicated pain and severity of functional disability as limiting duration and type of employment, although other studies indi-cated specific symptoms such as pain, joint function, and laboratory findings as nonpredictors of work limitations and cessation (5). Other factors associated with vocational success for persons with arthritis include support of coworkers, supervisors, and family members; perceived high job status; positive attitudes toward the job; workstation modifications; satisfactory transportation; and selfemployment (13,(15)(16). More common and effective accommodations reported were the ability to alter work hours, flexible scheduling, the ability to control the pace of work tasks, participation in decision making, fewer work place limitations (e.g., sitting and standing long periods, lifting, reaching, and repetitive tasks), the ability to modify tasks and workstations, assistance from others, medications, and changing jobs (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Another review of 9 studies of job retention for persons with chronic diseases also reported limited effectiveness of programs focused on work accommodations and self-efficacy (25). Regardless of the benefit of specific VR programs for persons with arthritis, persons with arthritis infrequently use VR services (16,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that people with arthritis frequently report arthritis-attributable activity limitations (13,14) and participation restriction in important domains, e.g., socializing (15), accessing transportation (16), social and leisure activities (17,18), and getting around the community (16,19). Associations between limitations, pain, joints affected, and other symptoms have been inconsistent in these studies; however, negative psychological impacts are regularly associated with arthritis (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the highest social participation, they reported the most service barriers, especially work-related barriers. Our prior analyses comparing people with arthritis disability with people with disability from other conditions had compatible results (50,51). The OthDisab group here was smaller (94%) because persons with heart disease disability were taken into analysis groups.…”
Section: Discussionmentioning
confidence: 53%
“…The big difference between Phase One and Phase Two questionnaires can also confuse readers. Overall, the questionnaire structure requires painstaking description in analyses (50,51).…”
Section: Discussionmentioning
confidence: 99%